Dimethyl fumarate vs fingolimod following different pretreatments: A retrospective study. Issue 2 (March 2020) - Diem, Lara; Daponte, Ariadne; Findling, Oliver; Miclea, Andrei; Briner, Myriam; Salmen, Anke; Gold, Ralf; Kilidireas, Constantinos; Chan, Andrew; Evangelopoulos, Maria Elftheria; Hoepner, Robert
Abstract : Objective: Despite frequent use of fingolimod (FTY) and dimethyl fumarate (DMF), studies comparing clinical efficacy and withdrawal rates of DMF and FTY concerning different pretreatment situations are rare. The aim of our study was to compare relapse occurrence and withdrawal rates of DMF and FTY in different pretreatment situations. Methods: Patients from 4 European centers were retrospectively identified and followed until the 1st relapse after treatment start or if no relapse occurred for a maximum of 2 years. Cox regression analyses adjusted for relapsing-remitting MS (RRMS) disease duration, sex, and region were performed for the following pretreatment situations: treatment naive or injectables or DMF/FTY or natalizumab. Results: Seven hundred thirty-two patients with RRMS (female/male: 2.4:1.0; DMF n = 409, FTY n = 323) were analyzed. Compared with FTY-treated patients, DMF-treated patients discontinued treatment more frequently mainly because of side effects (DMF/FTY: 29.3%/20.7%). Clinical relapses occurred in 24.5% of the patients within 24 months. Survival analysis demonstrated that compared with FTY treatment, DMF treatment was associated with an adjusted hazard ratio (aHR) for occurrence of relapse of 1.9 (95% CI 1.4–2.6, p < 0.001, n = 732). Stratification into pretreatment groups unmasked a higher relapse risk in DMF patients pretreated with natalizumab (aHR [95% CI] 4.5 [1.9–10.8], p = 0.001, n = 122) or to a lesser extend also in treatment-naive patients (aHR [95% CI] 1.9 [1.01–3.6], p = 0.045, n = 230). No differences were observed in patients pretreated with injectables or the respective other oral drug (injectables: p > 0.05, n = 341; other oral: p > 0.05, n = 39). Conclusions: DMF treatment was associated with higher clinical disease activity compared with FTY treatment. A subgroup analysis suggested beneficial effects of FTY in treatment-naive and patients pretreated with natalizumab.